"Learning is not the most important thing; it's to make them into human beings": Teacher identity in vocational schools in Israel. (September 2022) - Barak, Mirit Haybi; Shoshana, Avihu
Abstract: This article examined teacher identity in vocational schools through in-depth interviews with 17 teachers in Israel. Findings revealed how the caring discourse underlies these teachers' identities. The teachers reported their strategic abdication of fostering academic achievement. They described how their teacher identity differs from teachers in other educational contexts because of their holding low expectations of their students ("the most important thing is to be a human being"). The teachers' characterizing the students as at-risk youth and their families as dysfunctional informs these low expectations. The Discussion highlights the unintended consequences of a caring-based teacher identity on maintaining educational stratification. Highlights: Teacher identity was examined in vocational schools through in-depth interviews with 17 teachers in Israel. The main findings revealed how a caring discourse underlies teacher identity. Teachers reported strategically relinquishing the cultivation of academic knowledge. Characterizing students as at-risk youth and their family as dysfunctional helps explain teachers' low expectations. The discussion highlights the consequences of caring-based teacher identity on maintaining stratification.